2022
DOI: 10.1002/jmri.28438
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cystic Lesions on MRI: What Is The Likelihood of a Present or Future Diagnosis of Pancreatic Carcinoma?

Abstract: BackgroundPancreatic cystic lesions (PCLs) are followed for years due to older and likely biased works demonstrating a strong association with pancreatic carcinoma; more recent data are needed clarifying this relationship.PurposeTo determine the association between PCLs on MRI and a synchronous or future diagnosis of pancreatic carcinoma.Study typeSingle‐center retrospective cohort.PopulationA total of 192 patients (111 female, 58%) with median age 66 years (range 26–87 years) with PCLs on abdominal MRI from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 40 publications
(93 reference statements)
0
0
0
Order By: Relevance
“…Fifteen studies met the inclusion criteria, all of which were retrospective. 18,19,27,[33][34][35][36][37][38][39][40][41][42][43][44] PCLs on MRI with Pancreatic Carcinoma at the Time of Initial MRI Eight studies reported on PCLs with a PDAC at the time of initial MRI (Table 1). 27,[33][34][35][37][38][39]44 The median year of publication for the eight publications was 2017 (range, 2010-2022).…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Fifteen studies met the inclusion criteria, all of which were retrospective. 18,19,27,[33][34][35][36][37][38][39][40][41][42][43][44] PCLs on MRI with Pancreatic Carcinoma at the Time of Initial MRI Eight studies reported on PCLs with a PDAC at the time of initial MRI (Table 1). 27,[33][34][35][37][38][39]44 The median year of publication for the eight publications was 2017 (range, 2010-2022).…”
Section: Study Selectionmentioning
confidence: 99%
“…18,19,27,[33][34][35][36][37][38][39][40][41][42][43][44] PCLs on MRI with Pancreatic Carcinoma at the Time of Initial MRI Eight studies reported on PCLs with a PDAC at the time of initial MRI (Table 1). 27,[33][34][35][37][38][39]44 The median year of publication for the eight publications was 2017 (range, 2010-2022). All studies used single-center databases from Italy (N = 4), Bulgaria (N = 1), Canada (N = 1), Japan FIGURE 4: Forest plot illustrating the percentage of patients with pancreatic cystic lesions on MRI who were diagnosed with pancreatic adenocarcinoma on a future date while on surveillance, with 95% confidence intervals (95% CI).…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations